The effects of inter-vibrator interference on vibrator performance - Dean, Tim; Tulett, J.; Lane, D. (Wiley-Blackwell, 2016)
© 2016 European Association of Geoscientists & EngineersThe output from the hydraulic vibrators typically used for land seismic surveys is controlled by monitoring the acceleration measured by accelerometers mounted on the reaction mass and baseplate. The considerable energy output by such vibrators, which are coupled with the sensitivity of the accelerometers used, results in crosstalk if more than one vibrator is being used. In this paper, we present the results of a field experiment in which we measured the crosstalk between two adjacent vibrators. We found that the level of crosstalk was approximately -20 dB when the vibrators were adjacent but decreased with increasing frequency and separation. This result has implications for measurements of vibrator performance, source-signature deconvolution, and in particular, estimates of the total energy output by a fleet of vibrators.